THE INFLUENCE OF PRODUCT QUALITY, SERVICE QUALITY, AND PRODUCT INNOVATION ON PURCHASE DECISIONS(Case Study: Dian’s Rumah Songket and Endek Klungkung Bali) - I Made Edi Suryadarma; Ni Wayan Ekawati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This study aims to explore the impact of product quality, service quality, and product innovation on the purchasing decisions of customers at Dian's Rumah Songket and Endek. Employing a quantitative research design with an associative framework, the study focuses on the customers of Dian's Rumah Songket and Endek as its population. A total of 100 respondents participated, selected through a purposive non-probability sampling method. data for this research was gathered using a survey method, which included a questionnaire that addressed various aspects of product quality, service quality, product innovation, and purchasing decisions through multiple statements related to these variables. The findings reveal several significant insights: firstly, product quality has a positive and significant effect on purchasing decisions; secondly, service quality similarly influences purchase decisions positively and significantly; and finally, product innovation also has a noteworthy positive impact on customer purchasing decisions.